Lip Reconstruction - Owens, Winston R.; Quirarte, Diego M.; Gillipelli, Srinithya R.; Layon, Sarah A.; Bovill, John D.; Dvoracek, Lucas A. (Seminars in Plastic Surgery, 2024)
Lip reconstruction is challenging for plastic surgeons due to the unique functionality and aesthetic complexity of the lips within the lower third of the face. The etiology of lip defects varies from congenital to acquired causes of origin. The most common acquired cause of lip defects is resection of malignancy. Defects can present as various shapes and sizes and may affect any location on the lip. Each defect requires a full workup, and algorithms such as the rule of thirds, are commonly used to swiftly identify optimal reconstructive options. The goal of lip reconstruction is to ensure oral competence while restoring intricate, cutaneous landmarks. The approach to lip reconstruction makes use of many rungs of the reconstructive ladder. This article primarily focuses on repairing lip defects secondary to Mohs surgery; however, the reconstructive methods discussed are useful for lip defects of all causes. This article will review lip defect evaluation, reconstructive methods, common complications, and adjuvant therapies to ensure optimal lip function and cosmesis.
Keywords: lip reconstruction; Abbe flap; Bernard–Burow; Estlander flap; Karapandzic flap; Mohs surgery